Analysis of health planning theories – a systematic approach - Z., Nurhaliza; Mohamad Yusof, Nazatul Yusrina; Fauzi, Farah Fatin; Gilbert Netto, Ericson Netto; Ibrahim, Mohd Safwan; Anthony, N. T. R.; Sondaram, Navindra Kumar; Tukur, Nura; Abdul Manaf, Rosliza; Juni, Muhamad Hanafiah (Community Health Society Malaysia, 2017)
Background: This article examines the usage of various theories in the perspective of health planning. Accounts of transformation initiatives often reveal little about past organisational and contextual planning conditions that contributed to success. This article aims to explain the historical usage of planning theories by aligning them to the current healthcare system. Materials and Methods: A scoping review of literature using electronic database of PubMed, ScienceDirect, Google Scholar was done with special attention given to three specified planning theory in relation to health care planning. A total of 30 articles, reports and theses were selected and analysed. The analysis and findings are presented based on three different theories that has been selected which are the rational planning model, incremental planning theory and mix scanning planning theories. Result: Rational planning model is a process of understanding the problem followed by establishing and evaluating planning criteria, formulation of alternatives, implementing them and finally monitoring the progress of chosen alternatives. Incrementalism refers to the method of change by which many small policy changes are enacted over time in order to create a larger broad based policy planning. Compared to some of the other budgeting methods used in healthcare, it is one of the easiest to put in practice. Mixed scanning can be said to be much less demanding and detailed compared to rationalised decision making. However, it is more comprehensive and broader compared to incrementalism. Conclusion: Health planning involves a cycle of planning process in which the ultimate goal is to improve health status or optimise wellness of a community. Although mixed scanning theory with substance from incremental theory seems to be prominently used, one has to take into account all the current issues, goals and country current situations before deciding on the most relevant theory to be used.